Analytical Comparision between Single and Modular Fuel Cell Stack: Uniform Modular Cell Approch - Megavath Venkatesh Naik; Paulson Samuel (International Journal of Advances in Applied Sciences, 2017)
A single fuel cell (FC) produces a very small voltage of about 0.6 -0.8 V under normal operating condition, and hence several individual cells are connected in series as a stack to get higher voltages suitable for practical loads. The stacks are then connected in series to get required values of DC voltage. The FC performance varies with the operating parameters such as temperature, humidity, fuel flow rate, ageing and fuel non uniform concentration. The FC stack underperforms when there is presence of bad cell in it. The Presence bad cell in a stack limits the current handling capacity of other healthy cells when it’s connected as a conventional single stack. This can be overcome by connecting the fuel cells in uniform modular cell configuration. In this paper a Uniform Modular Cell Configuration (UMCC) is proposed to gain the maximum power from the stack and the conventional Single or Uni Stack Configuration (USC) is compared with the proposed structure. A detail mathematical analysis of comparing both methods is described. Further the superiority of the proposed method is proven by carrirying out the simulations under steady state operating condition of a FC stack feeding to a constant current load.